Photoinduced FeCl3‐Catalyzed Alkyl Aromatics Oxidation toward Degradation of Polystyrene at Room Temperature†. Issue 12 (23rd September 2021) - Zhang, Guoxiang; Zhang, Zongnan; Zeng, Rong
Main observation and conclusion: While polystyrene is widely used in daily life as a synthetic plastic, the subsequently selective degradation is still very challenging and highly required. Herein, we disclose a highly practical and selective reaction for the catalytically efficient oxidation of alkyl aromatics (including 1°, 2°, and 3° alkyl aromatics) to carboxylic acids. While dioxygen was used as the sole terminal oxidant, this protocol was catalyzed by the inexpensive and readily available ferric compound (FeCl3 ) with irradiation of visible light (blue LEDs) under only 1 atmosphere of O2 at room temperature. This system could further facilitate the selective degradation of polystyrene to benzoic acid, providing an important and practical tool to generate high‐value chemical from abundant polystyrene wastes. Abstract : We report a photoinduced FeCl3 ‐catalyzed protocol to facilitate the oxidation of alkyl aromatics (including 1°, 2°, and 3° alkyl aromatics) as well as polystyrene to carboxylic acids using dioxygen as the sole terminal oxidant under mild conditions.